Structuring, Design and Analysis of a Pentab and SIW Cavity Backed Antenna for Iot Applications - P. Cowsigan, S; Saraswady, D (International Journal of Engineering and Technology, 2018)
Substrate Integrated Waveguide (SIW) cavity backed antenna technology is a new form of transmission line facilitating the realization of non-planar (waveguide based) circuits into planar form for easy integration with other planar (Microstrip) circuits and systems. They retain the low copper and dielectric loss property of traditional metallic waveguides and are widely used in integration of walls, floors and flame redundant wearable. SIW-CB antenna is a perfect candidate for IoT based wearable antenna with FR4 substrate. In this sense we structurizean efficient small size antenna for IoT applications to operate in the range of 5 â€“ 15 GHz. FR4-epoxyÂ  substrate is chosen so that the losses are minimized hence improving the efficiency. The proposed antenna resonates at 5.4, 6.9,9.1,11.5 & 14.2 GHz hence forming the Pentaband with a maximum return loss of 38.6 db. The other antenna parameter values are Gain 28.5 db, efficiency 90% and VSWR 1.Â